Correlation between Interleukin-1β serum level with severity of airway obstruction in Exacerbation Chronic obstructive pulmonary disease (COPD) - Nurfajar Budi Mulya; Muhamad Ilyas; Erwin Arief; Irawaty Djaharuddin; Siti Nurisyah; Harry Akza Putrawan (Faculty of Medicine, Hasanuddin University., 2021)
Introduction: To observe the relation between Interleukin-1β with exacerbation of Chronic Obstructive Pulmonary Disease (COPD). Methods: This study was designed for a cross-sectional study. 65 acute exacerbation COPD patients were selected. The serum level of Interleukin-1β was recorded. Results: Most of the subjects are men (95,4%), moderate smokers (41,5%), normal BMI (61,5%), more than 60 years old (73,8%), have more than 2 exacerbations in a year (67%), severe airway obstruction (41,5%) and mostly in group D (80%). The mean level of Interleukin-1β was 1.63 pg/ml range from 0,009-17,62 pg/ml. Kruskal Wallis analysis test noticed significant differentiation mean serum level of Interleukin-1β in several groups of GOLD. p<0,05. There was no correlation between serum level of IL-1β with the severity of airway obstruction (GOLD) p>0.05. Conclusions: there was no correlation between the severity of airway obstruction with serum level of IL-1β in acute exacerbation of COPD. there was a vicious trend of increasing IL-1β serum level according to the severity of airway obstruction mainly seen in GOLD 2, GOLD 3, and GOLD 4.